iRGD-modified exosomes-delivered BCL6 siRNA inhibit the progression of diffuse large B-cell lymphoma - Liu, Qinhua; Dai, Guanrong; Wu, Yi; Zhang, Mingxia; Yang, Mingya; Wang, Xiaonan; Song, Mingyue; Li, Xiaodan; Xia, Ruixiang; Wu, Zhengsheng (Frontiers in Oncology, 2022)
Clinical applications of siRNA therapeutics have been limited by the immunogenicity of the siRNA and efficiency of siRNA delivery. Recently, evidence have shown that exosomes, endogenous nano-vesicles, can deliver siRNA to the tumor tissues in mice. Here, to reduce immunogenicity, we selected immature dendritic cells (DCs) to produce exosomes. In addition, tumor targeting was achieved by engineering the DCs to express exosomal membrane protein (Lamp2b), fused to av integrin-specific iRGD peptide (CRGDKGPDC). Next, iRGD targeted exosomes (iRGD-Exo) were isolated from the transfected DCs, and then the isolated exosomes were loaded with BCL6 siRNA by electroporation. Our results found that integrin (αvβ3) receptors were highly expressed on OCI-Ly8 cells. In addition, iRGD-Exo showed high targeting ability with avβ3 integrins positive OCI-Ly8 cells. Significantly, iRGD-Exo loaded with BCL6 siRNA suppressed DLBCL cell proliferation in vitro. Furthermore, intravenously injected iRGD-Exo delivered BCL6 siRNA to tumor tissues, resulting in inhibition of tumor growth in DLBCL. Meanwhile, exosomes mediated BCL6 siRNA delivery did not exhibit appreciable toxicity in mice. Collectively, our study demonstrates a therapeutic potential of exosomes as a promising vehicle for RNAi delivery to treat DLBCL.